'We are all in the image of God': reproductive imaginaries and prenatal genetic testing in American Jewish communities. (November 2020) - Ginsburg, Faye; Rapp, Rayna
Abstract: How are we to understand the complexities of prenatal genetic testing across social and cultural worlds? Availability and uptake of this biotechnology is variable, deeply influenced not only by national frameworks but also by local regimes of value. We argue that these intersections of genetic testing and local cultural worlds must be understood as part of broader 'reproductive imaginaries', including everything from kinship, pregnancy and gender norms to children's links to specific community norms of national and cultural futures. In the USA, preconceptual/prenatal genetic testing is widely available, driven by a neoliberal market-based model of consumer choice. In contrast, such tests are far more restricted by bioethical laws and medical regulations in France. This article will examine how particular cultural and religious communities – primarily American orthodox Jewish communities – shape prenatal genetic testing in their own distinct ways.